Boost rectifier using single phase matrix converter topology: article - Mohd Amin, Nur Nathassa (2012)
This paper presents work on the modeling. simulation and experimental test rig of single phase matrix converter topology as a single phase boost rectifier operation. The propose of this circuit is able to generate the output voltage greater than the input. This circuit employed eight Insulated Gate Bipolar Transistor switches connected in common emitter configuration in order to perform bidirectional operation. The pulse width modulation (PWM) technique was used to synthesize the output of the switching control algorithm by through calculating the switch duty ratio. The commutation strategy has been implemented with reduction in spikes, there was a common phenomenon that happens in matrix converter topologies. A simulation model is design using MATLAB/Simulink and the results of simulations and experimental test rig are presented to evaluate the behavior and feasibility of the proposed topology.